PERBANDINGAN SPUTUM BTA POSITIF DAN SPUTUM BTA NEGATIF TERHADAP FOTO TORAKS PADA PASIEN TB PARU - Situngkir, Jesica Damayanti; Damanik, Irene; Siahaan, Jekson Martiar (Jurnal Kedokteran Methodist, 2019)
Background : Pulmonary tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis with the main symptom of a cough with phlegm for 2 weeks or more. Coughing can be followed by additional symptoms, namely phlegm mixed with blood, coughing up blood, shortness of breath, weakness, decreased appetite, weight loss, malaise, night sweats without physical activity and fever for more than one month. Some suspicions in TB patients should be carried out immediately by routine sputum examination and chest X-ray. The occurrence of radiographic changes in smear negative and smear positive is very important in helping diagnose pulmonary TB.Method: The research method used was a Literature Review, using secondary data. The data collection method used in this research is the documentation method. The research journals used are 5 journals with inclusion criteria for pulmonary TB patients who carry out BTA examinations and chest photos and the date of publication ± the last 5 years starting from 2014 - 2019, then the language used in this research method is to use Indonesian and English, as well as full text publication journals.\Results: There is a difference in the extent of lesions on chest X-ray between smear positive pulmonary TB patients and smear negative pulmonary TB patients.